Tongan conceptions of schooling in New Zealand : insights and possible solutions to underachievement - 'Otunuku, Mo‘ale (ResearchSpace@Auckland, 2011)
An understanding of Tongans' conceptions of New Zealand secondary schooling is fundamental to behavioural and professional development interventions that may help promote academic achievement. The purpose of the thesis is to investigate Tongan attitudes, beliefs and intentions relating to their secondary schooling experiences in the context of New Zealand and how these constructs may or may not influence learning outcomes. A mixed methods analysis of parents, students and teachers' qualitative and quantitative data identified beliefs about aims of schooling, their responsibilities and school preferences and their conceptions of reasons for Tongan students' low achievement. The three participants' conceptions of assessment, teaching and learning were also identified with students' conceptions being analysed against their NCEA results. Measurement models for Tongan parents' conceptions of schooling were found for each of the seven domains investigated. Measurement models were also found for Tongan secondary school students' conceptions of assessment, teaching experiences and approaches to learning and teachers' conceptions of assessment, teaching and learning. The SEM analysis of Tongan students' conceptions of schooling and their NCEA results found that strength of predictors and proportion of variance explained was higher for the externally assessed component, there was a subject-based difference in how Tongan students' performance was influenced by their schooling conceptions and more Tongan students were doing internally assessed standards. Behavioural changes to support academic success can happen when peoples' current beliefs and attitudes are identified and made explicit. From these, appropriate behavioural or professional development interventions can be developed and implemented to bring about positive changes. Under current conditions, Tongans beliefs and attitudes about schooling experiences do not seem to generate good academic outcomes for Tongan secondary school students in New Zealand. Teachers' deficit theorizing of Tongan students is still an issue and identifying these constructs and understanding them are central to the government and school efforts to improve the academic achievement for Tongan students. In addition, schools should emphasize the competitive challenge of doing well in formal examinations as a means of leveraging Tongan community beliefs towards greater academic performance for Tongan students. This is to complement the current emphasis on cultural compatibility and responsive approaches already implemented.